Sistem Presensi Karyawan dengan Pemanfaatan Teknologi Geotagging pada PT. Swadaya Makassar (Perusahan Outsourcing Cleaning Service) - Suryadi Syamsu (Celebes Computer Science Journal, 2020)
This study aims to create a system that is able to report on the daily attendance of employees. The model chosen was in the form of attendance reporting and attendance home via smartphone.This system can automatically record and record attendance for a month which includes attendance, permission, illness or negligence. This method also makes it easy for companies to find information about cleaning service workers with detailed attendance and return and can make reports easily. The research method used is the use of the concept of geotagging by attaching coordinates to the details of an object image. The database used in this application is MySQL.In this study, a web-based employee attendance application is designed using a geographic information system to display the coordinates of the presence of employees who attend attendance and return attendance. In this way it is not possible for employees to attend but not in the workplace location because there is a supervisior in every company that controls attendance.